Inclusão escolar na percepção de professores do município de Dois Córregos, São Paulo - Gomes, Paulo César [UNESP]; Minguili, Maria da Glória (My University, 2014)
This paper aims to make a survey about the inclusion of children in need of special care in all schools and day nurseries (publics and privates) in ?Dois Córregos? city, in São Paulo. We interviewed 144 teachers and 14 school principals in 14 educational establishments ? 5 private schools, 5 state-owned schools, 2 municipal schools, 1 municipal nursery and 1 philanthropic nursery. The research aimed to investigate possible prejudices against the children in need of special care; verify if the schools have adequate infrastructure to receive the students in need of special care; and verify if the professionals who work in the schools are receiving (or received) specific training to work on this inclusion process. The results indicated that teachers who don?t work with children in need of special care are very insecure in receiving them. It?s evident that there are a lot of doubts and uncertainties about the inclusion system. In general, schools don?t have adequate infrastructure and most of the time the included students are those who have internal deficits, which are not evident.

Este trabalho teve por objetivo fazer um levantamento a respeito da inclusão de crianças com necessidades educacionais especiais (NEE) em todas as escolas e creches (particulares e públicas) da cidade de Dois Córregos ? SP. Foram questionados 144 professores e 14 diretores em 14 estabelecimentos de ensino, da creche ao Ensino Médio (sendo que dos estabelecimentos de ensino, 5 são escolas particulares, 5 são escolas públicas estaduais, 2 são escolas públicas municipais, 01 creche municipal e 01 creche filantrópica). A pesquisavisou a: investigar possíveis preconceitos existentes em torno da questão, verificar se o ambiente físico das escolas possui acomodações especiais necessárias para receber os alunos com necessidades educacionais especiais (NEE), além de averiguar se os profissionais que atuam na escola estão recebendo (ou receberam) capacitação específica para atuar no processo de inclusão desses alunos. Os resultados indicam que os docentes que não trabalham com alunos com NEE teriam uma grande insegurança em recebê-los.Ficou evidente que há muitas dúvidas e incertezas acerca da inclusão, as escolas não possuem infraestrutura adequada e muitas vezes os alunos incluídos são exclusivamente aqueles que possuem déficits internos e não aparentemente visíveis.
Educational inclusion in the perception of teachers of Dois Córregos, São Paulo
Keywords: Special educational needs; Inclusion; Integration; Necessidades educacionais especiais; Inclusão; Integração